2015
DOI: 10.1007/s11011-015-9694-9
|View full text |Cite
|
Sign up to set email alerts
|

The impaired synthesis of insulin and its inability to inhibit platelet aggregation in cerebrovascular accident

Abstract: Both ischemic stroke (IS) and hemorrhagic stroke (HS) are reported to occur due to thrombosis on the arteries of the brain. As diabetes mellitus is a risk factor for strokes and insulin is reported to prevent thrombosis, the role of insulin in IS and HS was investigated. Forty eight stroke victims (IS = 22, HS = 26) and equal number of aged and sex matched normal volunteers participated in the study. Nitric oxide was determined by methemoglobin method. Insulin and Dermcidin isoform-2 (DCN2) level was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This stress-induced protein, which was found in the circulation of AMI and ACS patients, was the platelet aggregator and the inhibitor of the aspirin effect through the impairment of nitric oxide [21,22]. We reported from our laboratory that dermcidin-induced hyperglycemia was due to the impairment of NO [44,45] which causes endothelial dysfunction relating to the elevated HbA1c [46,47]. Insulin, which is an anti-thrombotic factor, plays a very important role in the inhibition of AIHD [19,48] through the production of nitric oxide [49] by the expression of eNOS gene [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This stress-induced protein, which was found in the circulation of AMI and ACS patients, was the platelet aggregator and the inhibitor of the aspirin effect through the impairment of nitric oxide [21,22]. We reported from our laboratory that dermcidin-induced hyperglycemia was due to the impairment of NO [44,45] which causes endothelial dysfunction relating to the elevated HbA1c [46,47]. Insulin, which is an anti-thrombotic factor, plays a very important role in the inhibition of AIHD [19,48] through the production of nitric oxide [49] by the expression of eNOS gene [50].…”
Section: Discussionmentioning
confidence: 99%
“…So, despite the small sample size, it can be assumed from the above found results of clinical experimentation that dermcidin could be one of the responsible factors for the creation of prostate malignancy and concomitantly IR here. Previously, it was found that dermcidin impaired the insulin activity through NO inhibition [22,44] and the found result of elevated HbA1c level and lower level of NO are the indication of endothelial dysfunction which actually precipitates cardiovascular disease. Chest pain is the distinctive feature of AMI and low level of NO might be the causative factor of pain in AMI, and cTroponon is the well known marker of the occurrence of AMI.…”
Section: Discussionmentioning
confidence: 99%